A direct mechanochemical conversion of Pt-doped metal-organic framework-74 from doped metal oxides for CO oxidation. (March 2022) - Yi, B.; Zhao, H.; Cao, L.; Si, X.; Jiang, Y.; Cheng, P.; Zuo, Y.; Zhang, Y.; Su, L.; Wang, Y.; Tsung, C.-K.; Chou, L.-Y.; et al.
Abstract: Mixed-metal metal-organic frameworks (MM-MOFs) contain more than one type of metal node, which can improve or even introduce new features compared with the single metal frameworks. Traditionally, most of the MM-MOFs are synthesized by solution method which requires all the metal ions to form stable coordination with the ligand in a single framework and therefore limits the choice of the metal ions. In this work, Pt-doped Zn-MOF-74 (PtZn-MOF-74) has been prepared through a mechanochemical conversion approach from Pt-doped ZnO (Pt–ZnO) directly. The absence of a large quantity of solvent limits the solvation and diffusion of growth species during the mechanochemical conversion and therefore prevented the agglomeration of Pt dopants in PtZn-MOF-74. CO oxidation was used to evaluate the catalytic performance of the prepared MM-MOFs. Compared with inert Zn-MOF-74, PtZn-MOF-74 with unsaturated coordinated Pt at elevated temperature can act as the active sites to catalyze CO oxidation reaction. This study provides a novel design strategy for the synthesis of MM-MOFs with extended functionalities. Graphical abstract: Image 1